UV Protection and Antibacterial Properties of Yarn Coated with Polyvinyl Alcohol by Nip-rollers Process - Sriwittayakul, Worawit; Masae, Mahamasuhaimi; Keereetham, Pongpat; Onketpon, Wongsakon; Kongsong, Peerawas (RMUTP Research Journal Sciences and Technology, 2021)
The objective of this study is to explore a method to improve UV protection and antibacterial properties of the cotton yarn surface to produce high-quality textile products. Cotton yarns were coated with sodium hydrogen phosphate, magnesium chloride, softener solution and 0 to 0.54 M of polyvinyl alcohol to hold surface yarns to the yarn body using the winding machine. The coated yarns were analyzed using Field emission scanning electron microscope, Fourier transform infrared spectroscopy and UV-Vis spectrophotometer. Optimal results were achieved when coating with 0.45 M PVA exhibited UV protection was excellent protection. The cotton yarn coated 0.45 M polyvinyl alcohol displayed the antibacterial activity in the presence of Staphylococcus aureus and Escherichia coli was 87 and 91%, respectively. The expected overall properties may open the way towards new applications of high performance fabrics, leading to an innovative product development in the textile industry